Developing a feeding assay system for evaluating the insecticidal effect of phytochemicals on Helicoverpa armigera - Mohite, Sharada D.; Patil, Yogita P.; Nichit, Vikram J.; Joshi, Rakesh S. (Jove-Journal of Visualized Experiments, 2023)
Helicoverpa armigera, a lepidopteran insect, is a polyphagous pest with a worldwide distribution. This herbivorous insect is a threat to plants and agricultural productivity. In response, plants produce several phytochemicals that negatively impact the insect's growth and survival. This protocol demonstrates an obligate feeding assay method to evaluate the effect of a phytochemical (quercetin) on insect growth, development, and survival. Under controlled conditions, the neonates were maintained until the second instar on a pre-defined artificial diet. These second-instar larvae were allowed to feed on a control and quercetin-containing artificial diet for 10 days. The insects' body weight, developmental stage, frass weight, and mortality were recorded on alternate days. The change in body weight, the difference in feeding pattern, and developmental phenotypes were evaluated throughout the assay time. The described obligatory feeding assay simulates a natural mode of ingestion and can be scaled up to a large number of insects. It permits one to analyze phytochemicals' effect on the growth dynamics, developmental transition, and overall fitness of H. armigera. Furthermore, this setup can also be utilized to evaluate alterations in nutritional parameters and digestive physiology processes. This article provides a detailed methodology for feeding assay systems, which may have applications in toxicological studies, insecticidal molecule screening, and understanding chemical effects in plant-insect interactions.

Tyramine-mediated hyperactivity modulates the dietary habits in Helicoverpa armigera - Patil, Yogita P.; Gawari, Shyam K.; Barvkar, Vitthal T.; Joshi, Rakesh S. (JOURNAL OF CHEMICAL ECOLOGY, 2024)
Keywords: amines; Behavior; dopamine; octopamine; RECEPTOR; sensitivity; SULFAKININ

Altered Octopamine synthesis impairs tyrosine metabolism affecting Helicoverpa armigera vitality - Patil, Yogita P.; Wagh, Deepti S.; Barvkar, Vitthal T.; Gawari, Shyam K.; Pisalwar, Priyanka D.; Ahmed, Shadab; Joshi, Rakesh S. (Pesticide Biochemistry and Physiology, 2025)
Tyramine (1-hydroxylase (T(1H) is a key enzyme in the biosynthesis of octopamine (OA), a vital neurohormone in invertebrates. This study explores the expression patterns and functional role of Helicoverpa armigera T(1H (HaT(1H) across various tissues and developmental stages. HaT(1H expression was highest in the head and adult male stages, reflecting tissue-specific and developmental regulation. HaT(1H silencing significantly increased locomotion and decreased feeding behavior. OA supplementation in silenced insects or HaT(1H overexpression showed a contrary effect on locomotory and feeding behavior. In silico screening and inhibitory assays identified tomatidine, a tomato-derived metabolite, as a potent HaT beta H inhibitor with strong binding affinity. In vivo bioassays confirmed tomatidine's inhibitory effects, reducing feeding and increasing mortality in H. armigera. Modulation in HaT(1H expression or activity disturbs the tyrosine metabolic pathway, with altered levels of tyramine, octopamine, and dopamine. These results highlight HaT(1H as a key regulator of OA biosynthesis, influencing insect feeding, locomotion, and overall survival. The present study also introduces tomatidine as a potential candidate for insect control, given its ability to disrupt HaT beta H function. This work provides new insights into the physiological roles of HaT beta H and offers promising avenues for developing targeted pest management strategies.
Keywords: Helicoverpa armigera; Octopamine biosynthesis; Tomatidine; Tyramine (1-hydroxylase (HaT(1H); Tyrosine metabolic pathway

From signals to sustenance: the role of biogenic amines in insect feeding behavior - Patil, Yogita P.; Joshi, Rakesh S. (Journal of Insect Behavior, 2025)
Insect feeding is a complex and finely-tuned behavior that notably impacts their physiological and metabolic processes. Chemical signals and cues, chemosensation, motor response, and physiological changes govern responses to food resources. The role of biogenic amines in regulating feeding is essential, as they significantly affect locomotory changes and nutrient assimilation. Octopamine, tyramine, dopamine, serotonin, and other biogenic amines are neuromodulators, neurotransmitters, and neurohormones. Octopamine and tyramine have contrasting effects on food-seeking and foraging behavior regulation. The interaction among biogenic amines and their respective receptors initiates diverse signaling pathways by modifying the concentrations of intracellular secondary messengers like Ca2+, AMP, and other molecules. These signal transductions regulate various physical and metabolic processes, directly influencing feeding behavior and digestive physiology. Furthermore, dopamine triggers a negative response, whereas serotonin plays a positive role in regulating feeding behavior. Biogenic amines underlie synchronized and interconnected molecular mechanisms, along with unique individual effects. It is fascinating to consider these interrelated activities and the impacts of bioamine on insect feeding behavior. In this review, we discuss the roles of insect biogenic amines and their cross-talk in insect feeding and foraging behavior.
Keywords: Biogenic amines; feeding behavior; octopamine; Signal transduction; tyramine